(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND: Our objective was to measure hand bacterial contamination in a group of nursing and medical Italian students attending clinical wards for practical training, in order to verify the reliability of the information on hand hygiene (HH) adherence obtained by a self-reporting questionnaire. This questionnaire was administered with the aim to explore the effectiveness of basic education. METHODS: An anonymous questionnaire designed to investigate HH knowledge and practices was administered to a convenience sample of 100 nursing and 100 medical students. Data collected were combined with hand bacterial contamination measured both at the entry and the exit from the ward. RESULTS: HH practices and knowledge were significantly higher in nursing compared to medical students.. The most effective procedure in reducing bacterial contamination was the alternate use of handwashing and handrubbing compared to only one practice and the absence of hand hygiene (geom. mean: 180.3, 410.2 and 907.4 CFU/hand respectively, p<0.001). Hand contamination was significantly higher in students who declared to hardly ever/never implement HH teaching during clinical practice compared to those who stated to have done it frequently/always (geom. mean: 716 vs 277.1 CFU/hand, p<0.02). CONCLUSION: Our investigation adds something new to the topic of HH that is the measure of bacterial hand contamination to verify the reliability of the information obtained by questionnaire. The findings, pointing out some critical aspects in the HH teaching among healthcare students, highlight that solid knowledge results into correct behaviors, and consequently into a reduction of hand contamination.